Validasi media virtual tour sebagai alat peningkat kemampuan metakognitif siswa: hasil dan implikasinya - Masruri, Ahmad Bukhori; Sariyatun, Sariyatun; Sudiyanto, Sudiyanto (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
The increasing trend of technological innovation in learning media, in the Industrial Revolution 4.0 era makes it easier for students to access knowledge. Historical knowledge is vulnerable to becoming a pseudo-history which is usually narrated in connection with a historical heritage site. Students who do not have the ability to filter knowledge and are limited by direct access to the site will be vulnerable to being exposed to pseudo-history. This research aims to produce learning media that is suitable for use in the classroom. Media in the form of a virtual tour was chosen to facilitate access and improve metacognitive abilities as a filter for students. The research carried out was research and development (R&D) research with a 4-D approach, which was limited to the development stage due to time constraints. Data analysis based on the results of the media feasibility test assessment scores by curriculum expert validators and media expert validators. From a scale of 5, each score of 4.73 was obtained by curriculum experts. while a score of 4.82 was obtained by media experts. The research results show that virtual tour media is very suitable to be used as one of choice of learning media.